Morpho-functional traits of phytoplankton functional groups: a review - Welbara, Demtew Etisa; Gebre-Meskel, Demeke Kifle; Hailu, Tadesse Fetahi (Biológia, 2024)
This paper reviews more than 40 journal articles that describe the traits of phytoplankton functional groups (FGs) and their responses to biotic and abiotic factors in freshwater environments. Scholars have used different approaches with varying assumptions, making it necessary to subject the available information to a modest review. The paper sheds light on the potential responses of phytoplankton assemblages to biotic factors such as allelopathy, vertical migration, prey-predator interactions, macrophytes dominance, zooplankton grazing, and abiotic factors such as nutrient deficiency, turbulence and mixing processes, light, and temperature. It also highlights the status of studies on phytoplankton FGs in Ethiopian water bodies. While FGs have relevant applications in ecosystem assessment and monitoring, the difficulties faced are briefly discussed.